Les femmes, l’entreprise et le droit 2019: une décennie de réformes - World Bank Group (World Bank, 2019)
The World Bank Group’s Women, Business and the Law examines laws and regulations affecting women’s prospects as entrepreneurs and employees across 187 economies. Its goal is to inform policy discussions on how to remove legal restrictions on women and promote research on how to improve women’s economic inclusion. Women, Business and the Law 2019: A Decade of Reform introduces a new index measuring legal rights for women throughout their working lives in 187 economies. The index is composed of 35 data points grouped into eight indicators. The data covers a 10-year period not only to understand the current situation but to see how laws affecting women’s equality of opportunity have evolved over time. The index assesses economic rights at milestones spanning the arc of a woman’s working life: the ability to move freely; starting a job; getting paid; legal capacity within marriage; having children; running a business; managing assets; and getting a pension.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; discipline; droits des femmes*; entrepreneuriat; femmes*; périodes historiques; sciences de la gestion; thématiques; économie; égalité des sexes

Social provisioning as a starting point for feminist economics - Power, Marilyn (Feminist Economics, 2004)
The past decade has seen a proliferation of writing by feminist economists. Feminist economists are not identified with one particular economic paradigm, yet some common methodological points seem to be emerging. I propose making these starting points more explicit so that they can be examined, critiqued, and built upon. I use the term “social provisioning” to describe this emerging methodology. Its five main components are: incorporation of caring and unpaid labor as fundamental economic activities; use of well-being as a measure of economic success; analysis of economic, political, and social processes and power relations; inclusion of ethical goals and values as an intrinsic part of the analysis; and interrogation of differences by class, race-ethnicity, and other factors. The paper then provides brief illustrations of the use of this methodology in analyses of US welfare reform, gender and development, and feminist ecological economics.
Keywords: OFDIG; approches et analyses; discipline; droits des femmes*; genre; identités LGBTQIA2+; méthodologie; point de vue situé; ressource en ligne; sciences de la gestion; thématiques; économie

Travailler autrement : féminismes, travail et recherche-action - Institut de recherches et d'études féministes
Dans cet épisode, on explore les liens entre recherche-action, entrepreneuriat et santé au travail à travers une perspective féministe. Entre ateliers participatifs, mises en situation concrètes et discussions critiques, on interroge les inégalités de genre en entreprise, l’inclusivité au travail et les dynamiques de pouvoir dans le management. Comment accompagner autrement ? Comment transformer les pratiques plutôt que les adapter aux normes dominantes ? Une plongée dans les savoirs situés, les résistances quotidiennes et les pistes d’action pour un monde du travail plus juste. Avec: Christina Constantinidis, Mélina Dorval, Nancy Aumais, Jessica Riel, Evelyn McDuff Épisode enregistré durant la Foire féministe de l'IREF (27, 28 février et 1er mars 2025 - https://sites.grenadine.uqam.ca/sites/dsj/fr/foire-feministe-feministes-dans-la-cite) . Un épisode écrit et monté par Rajae Anys, avec le soutien financier du CRSH.
Keywords: EDI; approches et analyses; discipline; discours dominant; droits des femmes*; entreprenariat; foire féministe; recherches partenariales; santé; santé au travail; santé cardiovasculaire; sciences de la gestion; systèmes d'oppressions; thématiques; travail